Comparison of Intrathecal Bupivacaine Versus Bupivacaine plus Dexmedetomidine for Postoperative Pain Relief in Terms of Quality and Duration - Afzal, Zainab; Rao, Zahid Akhtar; Sameuddin, Syed; Khalid, Muhammad; Sultan, Muhsan; Saqib, Najm Us (Pakistan Armed Forces Medical Journal, 2025)
Objective: To measure the clinical efficacy of intrathecal Bupivacaine alone versus intrathecal Bupivacaine plus Dexmedetomidine on postoperative pain alleviation in terms of quality and duration in women undergoing C-section Study Design: Randomized controlled trial, (Iranian Clinical Trial Registry: 76165) Place and Duration of Study: Department of Anaesthesiology, PAF Hospital (Faisal), Karachi Pakistan from Sep, 2023 to Feb 2024. Methodology: After registration with trial registry (ICTR) and ethical approval, this randomized controlled trial was performed in Anaesthesia department of PAF Hospital (Faisal), Karachi. Intrathecal Dexmedetomidine was given as an adjuvant to Bupivacaine in 33 gravid ladies (Group A) after randomization. Group A and Group B patients were followed for 24 hours post-operatively to assess duration and quality of analgesia. Statistical significance was compared between both study Groups. Results: At twenty-four hours of time lapse, 2(6.1%) Group A patients had mild pain, 24(72.7%) had moderate pain and 7(21.2%) had severe pain compared to 7(21.2%) Group B patients who had moderate pain and 26(78.8%) had severe pain with p-value <0.001. The frequency of rescue analgesia was three times in 1(3.0) Group A and 10(30.3) Group B patients. The mean dose of analgesic ketorolac used by Group A patients was 53.64±23.4 milligrams with median dose of 60mg (IQR 30-120) compared to 110.91±19.099 milligrams in Group B with median dose of 120.0mg (IQR 60.0-150.0). Conclusion: We concluded that intrathecal Dexmedetomidine provides better postoperative analgesia in terms of quality and duration when used as an adjuvant with local anesthetic Bupivacaine.